Determination of Serum Interleukin-36 Alpha, Beta, Gamma, and Interleukin-17 Levels in Patients with Non-Hodgkin Lymphoma - Mehmet Şencan; Halef Okan Dogan; Ecem Demir; Hatice Terzi (Düzce Tıp Fakültesi Dergisi)
Aim: Non-Hodgkin lymphoma (NHL) is a diverse group of hematologic cancers characterized by uncontrolled proliferation of lymphoid cells. This study aimed to evaluate the relationship between serum concentrations of interleukin-36 alpha (IL-36α), interleukin-36 beta (IL-36β), interleukin-36 gamma (IL-36γ), and interleukin-17 (IL-17), which play an important role in the immune system, in NHL patients and whether these cytokines can serve as potential biomarkers or therapeutic targets for NHL.Material and Methods: A total of 88 individuals, including 55 NHL patients diagnosed and followed up in the Department of Hematology, Sivas Cumhuriyet University Medical Faculty, and 33 healthy controls, were included in the study. Blood samples were collected from patients at the time of diagnosis and from individuals in the control group for hemogram and biochemistry tests and serum IL-17, IL-36α, IL-36β, and IL-36γ levels. Patients were divided into three groups, complete remission (CR), partial remission (PR), and progression according to interim positron emission tomography/computed tomography (PET/CT) results.Results: Serum IL-36α (p